Risk Factors for Contralateral Occult Carcinoma in Patients With Unilateral Papillary Thyroid Carcinoma: A Retrospective Study and Meta-Analysis - Zhang, Fan; Zheng, Boyuan; Yu, Xiaohui; Wang, Xichang; Wang, Shiwei; Teng, Weiping (Frontiers in Endocrinology, 2021)
Background: Bilateral lesions are common in papillary thyroid carcinoma (PTC). For patients with unilateral PTC, occult carcinoma that is not detected preoperatively, but pathologically after surgery, might remain in the contralateral lobe. In this situation, inadequate surgical extent could cause relapse and even lead to re-operation. Here, we explore the frequency and investigate the risk factors of contralateral occult PTC in unilateral PTC through a retrospective study conducted by our team and published articles online, respectively. Methods: We collected patients’ clinical data in our hospital, whose cancer was determined to be confined to the unilateral lobe by preoperative image examination (N=204). These patients underwent initially total or near-total thyroidectomy and included their clinical data in the meta-analysis. We searched related literature in the PubMed, Embase, MEDLINE, Cochrane, and Web of Science databases until December 7, 2020, in order to perform a meta-analysis. The relevant articles were examined and the eligible studies were included to assess the association between clinicopathologic factors and contralateral occult PTC. Results: The meta-analysis included nine studies (involving 4347 patients). Of these, eight studies were from the databases and one study was our retrospective data. The meta-analysis showed that the prevalence of contralateral occult PTC was 26.6% in all patients. A tumor size > 1 cm, ipsilateral multifocality, contralateral benign nodule, and central lymph node metastasis were significantly associated with contralateral occult PTC. In contrast, sex, age, ETE, capsular invasion, BRAF mutation, Hashimoto thyroiditis, and lateral lymph node metastasis were insignificantly associated with contralateral occult PTC. Conclusion: The meta-analysis identified a tumor size > 1 cm, ipsilateral multifocality, contralateral benign nodule, and CLNM as being significant risk factors for contralateral occult PTC. These findings may guide the extent of surgery in unilateral PTC patients.